Free‐Electron Gas Spectrum Uniqueness in the Mixture of Noble Gases. Issue 2 (February 2016) - Stanković, K.; Alimpijević, M.
Abstract: Gas mixtures can reach the Maxwell's specter shape in case of low‐ionized mono‐atomic mixtures in the weak electric field. The parameters pertaining to the Maxwell spectrum of free electrons' gas straightforwardly settle on the insulating characteristics of the examined gas mixture at the fundamental level. In this paper, a condition for breakdown has been accomplished taking as a starting point the ionization coefficients derived accordingly, as well as the conditions for breakdown in keeping with the Townsend mechanism. The dc breakdown voltage value of noble gases mixture has been measured in the experimental part of the paper. The hypothesis that the free‐electron gas spectrum is unique in the noble gas mixture and is of Maxwell's type has been verified. (© 2016 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)